ASCOMYCETE FUNGI ISOLATED FROM PELTIGERA CYANOLICHENS OF SOUTHERN CHILE ... - Yosbany Pérez; Serey, Nayla; Millanes, Ana María; Lizana, Natalia; Katerin Almendras; Orlando, Julieta; Yosbany Pérez; Serey, Nayla; Lizana, Natalia; Orlando, Julieta (Instituto de Biodiversidad de Ecosistemas Antárticos y Subantárticos (BASE), 2023)
This resource is a report describing the identification and diversity of 43 fungi isolated from Peltigera lichen thalli (P. frigida, P. fuscopraetextata, P. rufescens, and P. antarctica) and 2 fungi isolated from Peltigera fuscopraetextata lichen substrate collected in southern Chile. The fungi were identified by sequencing the ITS marker and subsequent phylogenetic analyses, and a great diversity of ascomycete fungi was found, belonging to 6 classes, 12 orders, 13 families, and 16 genera. Only 33% of the strains were identified at the species level, 58% at the genus level, and 9% at the family level. Additionally, strains presumably belonging to new species yet to be described were also isolated. To our knowledge, this report represents the first record of these ascomycete fungi species on Peltigera lichens from southern Chile, and along with the deposited basidiomycete yeasts in this database, contributes to clarify the fungal diversity present in the Peltigera lichen mycobiome. Georeferencing was included ...